Báo cáo tình hình thực hiện các Nghị quyết của Quốc hội về Dự án hồ chứa nước Ka Pét, tỉnh Bình Thuận - Chính phủ (2024)
Toàn văn Báo cáo tình hình thực hiện các Nghị quyết của Quốc hội về Dự án hồ chứa nước Ka Pét, tỉnh Bình Thuận.